Nomenclatural review of names published in the fungal genus Dermoloma (Basidiomycota, Agaricales, Tricholomataceae) based on morphological analyses of type specimens - Michaela Caboňová; Marisol Sanchez-Garcia; Miroslav Caboň; Katarína Adamčíková; Pierre-Arthur Moreau; Alfredo Vizzini; Slavomír Adamčík; Soňa Jančovičová (Biodiversity Data Journal)
The majority of members of the fungal genus Dermoloma have been described, based on morphology and without molecular support. Sequencing most Dermoloma type specimens has been unsuccessful, probably due to degraded DNA, leaving their taxonomy primarily reliant on morphological characters. In this study, we re-described nine Dermoloma types, providing standardised morphological descriptions that include observations of previously undocumented microscopic structures.The pileipellis structure of D. hybridum, D. inconspicuum and D. intermedium var. coniferarum differs strongly from the typical Dermoloma pileipellis and these taxa do not belong to this genus. Dermoloma atrobrunneum and D. hymenocephalum are distinct taxa which have not been reported recently. The concept of Dermoloma cuneifolium var. punctipes is based on the presence of dark spots on the stipe. However, our examination of the type material reveals that its spores are more consistent with those of D. atrocinereum, a species that can also exhibit dark dots. Dermoloma longibasidiatum is likely a synonym of this species as well. The name D. pseudocuneifolium has been misapplied for a species with amyloid spores, but the type has inamyloid narrow spores characteristic for D. bellerianum. Dermoloma pragense probably represents a distinct, but recently unrecorded European species defined by large basidiomata and small spores. The data presented here are essential for future nomenclatural treatments within Dermoloma, as current phylogenetic studies suggest the presence of a large number of undescribed species.